Accommodating Embodied Thinkers. (16th February 2021) - Tanton, Tobias
Abstract: The principle of divine accommodation posits that revelation is accommodated to human cognitive capacities. It is regularly cited throughout the history of theology as an exegetical tool, as a doctrinal rationale, or as a condition for theological knowledge in general. This article proposes that divine accommodation invites an engagement with cognitive science, since findings in cognitive science illuminate the human cognitive capacities to which theological knowledge is accommodated. This article aims to demonstrate the fruitfulness of such an engagement by considering how theological concepts might be accommodated to accounts of human conceptualisation emerging from cognitive science. In particular, a case study considers the 'conceptualisation hypothesis' from 'embodied cognition', an emerging paradigm in cognitive science. This hypothesis suggests that human concepts are 'grounded' in sensorimotor states. If this scientifically‐motivated theory applies to all human concepts, it poses a potential theological dilemma: namely, if God‐concepts are grounded in sensorimotor states they prima facie risk being idolatrous, whereas if they are not so grounded, they may be un‐conceptualisable by humans. I suggest that one way to address this dilemma is to draw upon Athanasius' insight that the incarnation plays a crucial role in accommodating human understanding. By examining the incarnation as an accommodation to human capacities uncovered by cognitive scientists, we gain a more comprehensive account of the epistemological reason for the incarnation. This account offers new lines of thinking about debates on the doctrine of the incarnation, such as the possibility of multiple incarnations.